Analisis Faktor-Faktor Yang Mempengaruhi Volume Ekspor Kopra Di Indonesia - Fransisca Putri Dwiyani; Akhmad Baihaqi; Mustafa Usman (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Copra is one of the plantation commodity sub-sectors, a leading export commodity with a high production level. However, the high production of copra is not comparable to Indonesia's copra exports which are still very low. This study aims to determine what factors affect the volume of copra exports in Indonesia. The data used in this study is secondary data with the type of time series data from 2000-2019. This study uses multiple linear regression analysis. This study indicates that the volume of copra exports in Indonesia is influenced by domestic copra production, domestic copra prices, international copra prices, domestic copra demand, and exchange rates. The variables of domestic copra production, international copra prices, and domestic demand partially have a significant effect on the volume of copra exports in Indonesia. Meanwhile, the domestic copra price and the crucible exchange rate did not significantly affect the volume of copra exports in Indonesia. The domestic copra production variable is the most dominant variable affecting the volume of copra exports in Indonesia.